Full thickness genital burns independently increase the odds of death among pediatric burn patients. Issue 2 (April 2020) - Jimbo, Masaya; Overholt, Tyler L.; Cosma, Gabriela L.; Hudak, Steven J.; Granberg, Candace F.; Gargollo, Patricio C.
Summary: Background: There are limited published data characterizing pediatric burn patients with genital burns (GB). Objective: Assess prevalence of GB in pediatric burn patients and analyze clinical characteristics including predictors of mortality. Study design: We queried American Burn Association's National Burn Repository to identify all pediatric burn patients who presented to North American burn centers over a 10-year period. We excluded all patients aged ≥18 years and patients with unknown sex, race, and/or mortality. We also excluded subsequent encounters for patients with multiple visits. Demographic and clinical characteristics were compared between patients with and without GB. Univariable and multivariable logistic regression analyses were performed to identify predictors of mortality. Results: Among 38 211 pediatric burn patients, 1244 (3.3%) suffered from second- or third-degree GB. Patients who suffered from third-degree GB (GB3) were significantly older than patients who suffered from second-degree GB (GB2) or patients without GB. Of the patients, 32.3% were aged 0–2 years. Scalding was the most common mechanism of injury for pediatric GB patients at 73.8%. Compared to non-GB patients, GB patients had significantly higher total body surface area (TBSA) burned (16.5% vs 7.0%), higher rates of associated inhalation injury (4.1% vs 2.6%), longer length of stay (LOS) (14.3 days vs 6.7 days), higher rates of urinary tract infection (UTI) (13.0% vs 2.8%) and sepsis (14.1% vs 2.3%), and higher mortality (3.5% vs 0.7%) ( P < 0.0001 for all). The differences were more pronounced for the subset of patients who suffered from GB3 (TBSA 43.5%, associated inhalation injury 19.9%, LOS 42.9 days, 21.3% UTI, 33.3% sepsis, and 19.3% mortality). On multivariable analysis, the presence of GB3, TBSA, non-white ethnicity, and the presence of associated inhalation injury were significant predictors of mortality. Only 4.5% of pediatric GB patients underwent genital surgery, with the majority consisting of excision, reconstruction, or repair of the penis, vulva, or perineum. No patient required orchiectomy or suprapubic catheter placement. Discussion: This is the largest study to date of pediatric GB patients. A minority of pediatric burn patients present with GB. However, when they occur, GB are associated with significantly worse clinical outcomes. Importantly, the presence of GB3 is an independent predictor of mortality in pediatric burn patients. Conclusion: The presence of GB appears to be a strong marker of severe burn injury. Pediatric GB patients need to be carefully assessed and aggressively managed for additional injuries, complications, surgical needs, and mortality risk. Multivariable analysis of risk factors for mortality in pediatric burn patients. OR 95% CI P value GB3 present 1.88 1.01–3.49 0.0451* Age 1.01 0.99–1.04 0.3674 TBSA 1.05 1.05–1.06 <0.0001* Male sex 1.30 0.97–1.74 0.0823 Non-white ethnicity 1.46 1.08–1.96 0.0134 Inhalation injury 7.64 5.45–10.71 <0.0001* OR = odds ratio; CI = confidence interval. * indicates statistical significance.